Deltora shadowlands - Rodda, Emily (Rodda, Emily. Deltora shadowlands, 2009)
Though the Shadow Lord's tyranny over Deltora has ended, it's up to Lief, Barda, and Jasmine to rescue the Deltorans still enslaved in the Shadowlands.